Los Fantasmas que nos Persiguen: Judicialización del Arbitraje: ¿Un Problema Latente o Superado? - Limas Calderón, Sherin (Pontificia Universidad Católica del Perú, 2016)
This article is about the situation of the arbitration activity in Peru and how this development is affected by the phenomenon of the Judicialization. In the first part of the article, it questioned the jurisdiction attributed to arbitration. In the second part it approaches the theories of the nature of arbitration and its importance. Finally, it concludes with the concept of the judicialization and its impact on the arbitration.
The Phantoms that Chase Us: Judicialization of Arbitration: A Latent or Overcome Problem?
Keywords: Arbitraje; Judicialización; Jurisdicción; Extrapolación; https://purl.org/pe-repo/ocde/ford#5.05.00